Screening rice varieties for resistance to aluminum toxicity - Fageria, Nand Kumar; Zimmermann, Francisco José P. (Pesquisa Agropecuaria Brasileira, 2014)
Thirty upland rice cultivars were screened for aluminum tolerance in the nutrient solution at 0, 10, 20, 40 and 60 ppm aluminum concentrations. The effects of the AI on the dry matter production of the tops and roots and length of roots and tops were ascertained. Regression models were fitted to the root length data to group varieties on the basis of their susceptibility to AI toxicity. On the basis of regression, testes varieties were placed in group having high, medium and low tolerance to aluminum.